Hepatobiliary cancers and immunotherapy: where are we now and where are we heading? - Zayac, Adam; Almhanna, Khaldoun (Translational Gastroenterology and Hepatology, 2019)
Primary liver cancers are a heterogenous collection of diseases with variable natural histories and treatments. This review article will focus on hepatocellular carcinoma (HCC), intrahepatic and extrahepatic cholangiocarcinoma, and gallbladder cancer, and the use of immune checkpoint inhibitors (ICIs) in their treatment. This will include the currently studied, approved uses as well as the potential future roles of ICIs in the treatment of cancers of the hepatobiliary system through recent updates on ongoing studies and discussion of phase III studies underway. Currently, only two ICIs are approved for use in hepatobiliary cancers: nivolumab and pembrolizumab. First, pembrolizumab was approved for either microsatellite instability-high (MSI-H) or DNA mismatch repair deficient (dMMR) unresectable, or metastatic solid tumors, including HCC and biliary tract cancer (BTC) in May 2017. After CheckMate-040, nivolumab gained approval in late 2017 in the second-line setting for patients with advanced HCC and Child-Pugh A or B7 liver disease. Pembrolizumab was granted FDA approval in 2018 in the second-line setting after publication of KEYNOTE-224 for patients with advanced HCC and Child-Pugh A liver disease. All three approvals were independent of PD-L1 tumor or immune cell expression. Several other ICIs have been studied in various aspects of these diverse diseases including resectable disease and the advanced, unresectable, or metastatic setting from first-line to later line after failed systemic therapies. Some of these agents are also being assessed in combination with currently utilized tyrosine kinase inhibitors (TKIs) and/or chemotherapy. Lastly, we draw attention to phase III clinical trials in ICIs that are currently recruiting and will be approaching completion in the next 5 years, potentially altering the landscape of treatment in hepatobiliary malignancies for generations to come.